Pelatihan Pengolahan Kopi Manual Brew, Latte Art dan produk olahan Kopi Dengan Mesin - Rezki Alhamdi; Dewi Aurora Mikasari; Natal Olotua Sipayung; Taufik Bachrul Ulum Lubis (JURNAL KEKER WISATA, 2023)
The business opportunity of selling coffee drinks is quite good, this is evidenced by the many coffee outlets in several places. The coffee outlets that we can find are usually in the form of cafes, coffee shops, or just stands that offer a limited selection of coffee. this has a positive impact on both coffee drink sellers, distributors and coffee farmers. There is a lot of knowledge that we can get and develop from this coffee drink which in the end can provide economic benefits for coffee drink businesses. We can give this knowledge to several people who have the desire and pursue the profession and business of drinking coffee. One of the suitable places to be given education about the knowledge of both coffee beans and drinks is SMA. SMA is the last education before and female students go on to college or want to find a job. one of the favorite high schools in Batam City is SMAK Yos Sudarso. SMAK Yos Sudarso is a high school that has quite a lot of students. The Batam Tourism Polytechnic has the opportunity to provide education and training to students there. students and female students are given education about coffee drinks and coffee beans, then later students and female students are shown and demonstrated how to make processed coffee drinks using machines and also made manually. and finally the point is how to make latte art.